Pengaruh Kecerdasan Emosional terhadap Kecemasan Akademik: Studi pada Mahasiswa Universitas X di Jakarta - Gabriella Anniza Suhendro; Agustina Agustina (Fakultas Psikologi Universitas Tarumanagara, 2022)
The Covid-19 pandemic has changed the learning system in Indonesia, which was originally a face-to-face system to a distance learning system. This turned out to have a psychological impact on students, one of which was anxiety from the academic side. In a study conducted by Christianto et al. (2020) showed that as many as 50.4% of students who underwent online learning experienced moderate levels of anxiety. According to interviews conducted, students of the 2020/2021 class feel anxious when presenting online because they are worried that the internet network will have problems. With all the problems that arise during distance learning, emotional intelligence is needed to control any anxiety or difficulties encountered (Agus, 2019). The purpose of this study was to determine how much influence emotional intelligence has on academic anxiety in students of the 2020/2021 class during distance learning. This type of research is quantitative. This study involved 110 respondents using convenience sampling technique. For the emotional intelligence variable, the researcher used a measuring instrument that developed Daniel Goleman's theory (2014) and for the academic anxiety variable, the researcher used a measuring instrument that developed Holmes's theory (2010). Linear regression results show that R2 is 0.220 which means that there is an influence of emotional intelligence on academic anxiety by 22% and the other 78% is influenced by other factors.